The passion of the Christ - Bellucci, Monica, 1968-; Caviezel, Jim, 1968-; Davey, Bruce,; Fitzgerald, Benedict, 1949-; Gibson, Mel,; Gibson, Mel,; Gibson, Mel,; Morgenstern, Maïa, 1962- (Newmarket Films, 2004)
A graphic account of the trial and execution of Jesus Christ.